Effective Remediation of Copper(II) from Aqueous Medium Using A Polymeric Matrix: Optimization via Box-Behnken Design. - Tedjani Aicha Khairani Sara Khalifa Hizia (University of Shahid Hama Lakhdar - El Oued, 2025)
The remediation of heavy metals remains a global challenge facing water environmental management amidst the growing demands of industrialization. In this study, Schiff’s base chitosan adsorbent has been developed for the efficient removal of Cu2+ ions from the aquatic environment. A two-step process: loading with zinc oxide followed by crosslinking with 2-Hydroxy-1,2-Di(phenyl)Ethanone, were performed to synthesize the developed adsorbent, designated as CHI-HDE/ZnO. A batch approach was adopted using Box-Behnken design (BBD) to optimize the highest adsorption capacity of Cu2+ ions by CHI-HDE/ZnO under multivariable environments. Surface analysis results revealed that the surface area of CHI-HDE/ZnO (3.762 m2/g) was multiplied by 5.6 times compared to the original CHI material (0.401 m2/g). Based on both thermodynamic state functions: Gibbs free energy change ( ΔG = − 3.76, − 5.02, − 5.54, and − 6.12 kJ · mol−1 at 303, 313, 323, and 333 K, respectively), and the Entropy change (ΔS = 76.7J · mol−1 · K−1 ), the interaction between Cu2+ ions toward CHI-HDE/ZnO surface is a spontaneous process, accompanied by heat absorption of 19.0 kJ · mol−1. The pseudo-second-order model well fitted the experimental kinetic data. Furthermore, the CHI-HDE/ZnO adsorbent demonstrated a maximum adsorption capacity of 327.8 mg · g−1 for Cu2+ ions removal at 323 K, according to the Langmuir isotherm model. These results will offer promising prospects for aquatic environmental organizations, CHI-HDE/ZnO, as a promising adsorbent capable of effectively removing heavy metals, including Cu2+ ions, from the aquatic environment لا يزال معالجة المعادن الثقيلة تحديًا عالميًا يواجه الإدارة البيئية للمياه في ظل الطلب المتزايد للتصنيع. في هذه الدراسة، تم تطوير مادة شيتوزان القائمة على قاعدة شيف كمادة مازة لإزالة بكفاءة من البيئة المائية. تم تصنيع المادة المازة المُطورة المُشار )Cu أيونات النحاس الثنائي )+ 2 - عبر عملية من خطوتين: التحميل اكسيد الزنك يليه التشابك مع 2 CHI-HDE/ZnO إليها باسم هيدروكسي- 1،2 -ثنائي)فينيل( إيثانون. تم اعتماد منهج الدُفعات باستخدام تصميم بوكس-بهنكن في بيئات CHI-HDE/ZnO بواسطة Cu لتحسين أعلى سعة امتزاز لأيونات + 2 )BBD( CHI-HDE/ZnO متعددة المتغيرات. كشفت نتائج التحليل السطحي أن المساحة السطحية ل غرام(. /² غرام( قد تضاعفت بمقدار 5.6 مقارنة بمادة الشيتوزان الأصلية ) 0.401 م /² 3.762 م ( -، 5.02- ،3.76-،=ΔG ( استنادًا إلى دالتي الحالة الثرموديناميكية: التغير طاقة جيبس الحرة 323 ، و 333 كلفن على التوالي(، والتغير ،313 ، 5.54 ، و− 6.12 كيلوجول/مول عند 303 CHI- وسطح Cu كلفن(، فإن التداخل بين أيونات + 2 · جول/مول ΔS = الإنتروبي ) 76.7 كانت عملية تلقائية مصحوبة بامتصاص حراري مقداره 19.0 كيلوجول/ مول. HDE/ZnO تمثل نموذج الدرجة الثانية الزائف أفضل ملاءمة للبيانات الحركية التجريبية. علاوة على ذلك، سعة امتزاز قصوى بلغت 327.8 ملغ/غرام لإزالة CHI-HDE/ZnO أظهرت المادة المازة عند 323 كلفن وفقًا لنموذج لانجمير الآيزوثارم. تقدم هذه النتائج آفاقًا واعدة Cu أيونات + 2 مادة مازة واعدة قادرة على إزالة CHI-HDE/ZnO للمنظمات البيئية المائية، حيث تُعتبر من البيئة المائية بكفاءة. ،Cu المعادن الثقيلة، بما في ذلك أيونات
Master's theses in chemical engineering
Keywords: Schiff’s base chitosan; Box-Behnken design; Adsorption; Cu2+ ions; Isotherm models.; شيوزان قاعدة شيف، تصميم بوكس-بهنكن، الامتزاز، أيونات النحاس الثنائي نموذج ايزوثارم. ،Cu2+